Corporate Governance and Executive Compensation for Corporate Social Responsibility - Hong, Bryan (Journal of business ethics, 2016)
We link the corporate governance literature in financial economics to the agency cost perspective of corporate social responsibility (CSR) to derive theoretical predictions about the relationship between corporate governance and the existence of executive compensation incentives for CSR. We test our predictions using novel executive compensation contract data, and find that firms with more shareholder-friendly corporate governance are more likely to provide compensation to executives linked to firm social performance outcomes. Also, providing executives with direct incentives for CSR is an effective tool to increase firm social performance. The findings provide evidence identifying corporate governance as a determinant of managerial incentives for social performance, and suggest that CSR activities are more likely to be beneficial to shareholders, as opposed to an agency cost.